Correction to: Ethnobotanical characterization of medicinal plants used in Kisantu and Mbanza-Ngungu territories, Kongo-Central Province in DR Congo - Kibungu Kembelo Pathy; Nzuki Bakwaye Flavien; Belesi Katula Honoré; Wouter Vanhove; Patrick Van Damme (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article.